Changes in Carbohydrate Metabolism and Bulb Growth as Induced by Low-Temperature Release of Dormancy in Lily Bulbs - Zhang, Ya Juan (Philippine Agricultural Scientist, The (Formerly the Philippine Agriculturist), 2011)
The release of lily bulbs from dormancy is an important factor in their development. Dormancy which may develop after harvest, can be broken by storage for several weeks at a low temperature but the exact requirements to break dormancy are unknown. This study investigated the effects of cold treatments and non-cold treatments on dormancy of the bulbs of the oriental lilies 'Siberia and 'Conca d'Or'. Data from two lily cultivars (as necessary for model calibration and validation) were gathered after Iong-term storage over a wide range of storage temperatures [25 °C, 10 °C, 2 °C, and at fluctuating temperature (FT) during which bulbs were stored for 15 d at 10 'C and then at 2 °C until the 91st day]. Sugar and starch contents in the bulbs stored at different temperatures were measured, including plant quality parameters after the bulbs were planted. During storage exposure to low temperatures induced the net breakdown of starch and the accumulation of sucrose and fructose in the lily bulbs. This phenomenon is known as low temperature sweetening. Starch content, total soluble sugar and fructose changed more in the outer scales than in the inner scales at 4 °C for 'Siberia'. Bulb sweetening was especially pronounced in the 2 °C and FT treatments for the two cultivars. After low temperature storage, 100% of the bulbs of both cultivars sprouted, but the time to emergence was different, with bulbs of 'Siberia' emerging a week later than those of Conca d'Or, For horticultural applications or production purposes, storage at FT was better than other temperatures for lily. Moreover, 80 d cold treatment could release bulb dormancy in the two cultivars. Meanwhile, no shoot emergence was observed in bulbs stored at 25 °C. Our sstudy confirmed that carbohydrates had a positive relationship with dormancy release in oriental lily bubs.